Aligning higher education language policies with lecturers' views on EMI practices: A comparative study of ten European Universities. (February 2022) - Orduna-Nocito, Elena; Sánchez-García, Davinia
Abstract: As a result of the internationalization of higher education (HE), universities are implementing far-reaching changes such as the adoption of English-medium instruction (EMI) programs. In this new educational scenario, teachers are one of the agents most affected, as they clearly experience how the change in the language of instruction impacts their teaching and their students' learning. Although many universities are drafting policies to guide their academic staff in this process, what remains to be examined is whether teacher's views and experiences are aligned with what these policies determine, if they are complementary or far removed from each other. By adopting a qualitative approach, this paper sets out to analyze the current (mis) alignment between EMI language policies and teachers' practices as reported by 28 lecturers in 10 HEIs across Europe, taking part in an online teacher education program. Drawing on thematic analysis, three main categories emerged in the data examined. Findings reveal that the gap between top-down policies and bottom-up classroom experiences is still a reality that needs to be bridged. Some implications can be drawn from the study such as the need to redefine the diverse roles that English plays in this educational context and to include new contents in the training lecturers and students receive and, finally, the inclusion of top-down and bottom-up perspectives in the drafting of new policies.